Treasures of China : the glories of the Kingdom of the Dragon - Chinnery, John D. (Duncan Baird Publishers, 2008)
Charts the development of decorative arts and crafts in China, and the accompanying growth of ideas spiritual, philosophical, and political. Each chapter balances history with commentary that explains the art forms and reveals the nature and significance of their rich symbolism.